KISAH EYANG KUDO KARDONO MEMBENTUK KEBUDAYAAN MASYARAKAT TEGALSARI PERSPEKTIF TEORI STRUKTURALISME LEVIS-STRAUSS - Maida Aisha Rachmadianti (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: People have various types of culture in each region of this archipelago. It cannot be denied that a culture and tradition actually has an entity that is created from people's belief in a story, whether myth or legend. This is what makes this phenomenon interesting to study further. The aim of this research is to explore the current state of the Tegalsari (Surabaya) area, the legendary story of Grandpa Kudo Kardono from both an emic and historical perspective, and the existence of Grandfather Kudo Kardono's offering place. This research uses historical research methods and an ethno-archaeological approach. Then it uses the structuralism theory of Levi-Strauss along with its supporting theories, namely the semiotic theory by Charles Sanders Peirce and the theory of cultural interpretation by Clifford Geertz as an analytical tool. The results of the research include: there are 7 elements of universal culture as stated by Koentjoroningrat in an area in Tegalsari, Surabaya; the legend of Kudo Kardono, who is believed by the public to be the Majapahir warlord who succeeded in defeating Ra Kuti, although his name is not recorded in history; and the Grandfather Kudo Kardono Islamic Boarding School is located on Jalan Cempaka No. 25 and has artifact symbols, characteristics and traditions in it.